Unraveling the species diversity and relationships in the Leptodactylus mystaceus complex (Anura: Leptodactylidae), with the description of three new Brazilian species - Da Silva, Leandro A.; Magalhães, Felipe M.; Thomassen, Hans; Leite, Felipe S.F.; Garda, Adrian A.; Brandão, Reuber A.; Haddad, Célio F.B. [UNESP]; Giaretta, Ariovaldo A.; De Carvalho, Thiago R. [UNESP] (Magnolia Press, 2020)
Members of the Leptodactylus mystaceus species complex are widely distributed in forests and open formations of South America east of the Andes. Species of the complex are morphologically similar or indistinguishable among each other, but acoustic data have been the cornerstone for species discrimination across their geographic ranges. In this paper, we re-examine the monophyly, species diversity, and relationships in the L. mystaceus complex on the basis of morphology, coloration, acoustics, and DNA sequences. Morphological and color patterns originally used to the allocation of species to the L. mystaceus complex are also reassessed. Our results revealed three new species from the Brazilian Atlantic Forest and Cerrado, which are named and described herein, based mainly on acoustic and molecular data. Populations assigned to the lineage widely distributed across the South American Dry Diagonal (DD), reported in this study as L. cf. mystaceus, is likely paraphyletic with respect to the nominal species (Amazonian lineage), but additional data are still needed to address the taxonomic status of the DD lineage.
Keywords: Amazonia; Atlantic Forest; Bioacoustics; Biodiversity; Cerrado; Cryptic diversity; Dry Diagonal